THE INFLUENCE OF OCCUPATIONAL HEALTH AND SAFETY AND SUPERVISION ON EMPLOYEE PERFORMANCE OF PT. PAN MARITIME WIRA PAWITRA CREW MEMBERS - Daman Sudarman (Transpublika Publisher, 2023)
The purpose of this research is to investigate, test, and analyze the impact of occupational health, safety, and supervision on the performance of ship crew employees at PT. Pan Maritime Wira Pawitra. This research follows an associative approach with a quantitative method. The sample consists of 70 employees and crew members of PT. Pan Maritime Wira Pawitra, using a population sampling technique. Data was collected using a validated and reliable questionnaire. Multiple regression analysis was employed for data analysis. The findings of this study indicate that occupational health, safety, and supervision have a positive and significant effect on employee performance. Specifically, occupational health and safety positively and significantly affect employee performance. This is evident from the calculated t-value of 3.876, which is greater than the t-table value of 1.668. Moreover, the significance value (sig.) is 0.00, which is less than 0.05 (0.00 < 0.05). On the other hand, supervision has a positive but not very significant effect on employee performance. The calculated t-value of 0.21 is greater than 0.05, and the significance value is 0.21, also greater than 0.05. In conclusion, occupational health, safety, and supervision have a positive and significant impact on the performance of ship crew employees at PT. Pan Maritime Wira Pawitra. The F-value of 45.833 is greater than the F-table value of 3.13, and the significance value is 0.000, which is less than 0.05 (0.000 < 0.05), as obtained from the coefficient of determination results.